FAKTOR-FAKTOR YANG MEMPENGARUHI PERKEMBANGAN MOTORIK ANAK USIA 1-3 TAHUN DI DESA PULAU TINGGI KEC. KAMPAR KAB. KAMPAR - putri wulandini s; Sukarni (LPPM Universitas Abdurrab, 2025)
Early childhood is also called the golden age where at this age there is a very amazing and best development throughout human life. Factors that influence growth and development consist of internal and external factors. The purpose of the study was to determine the factors that affect the motor development of children aged 1-3 years with developmental delays in Pulau Tinggi Village, Kampar District, Kampar Regency. This type of research is quantitative with a descriptive research design. This research was conducted at Posyandu Bina Citra Desa Pulau Tinggi, Kampar District, Kampar District. The population in this study was 40 respondents. Data collection method using questionnaire sheets. The results showed that there are 5 factors that can affect children's motor development, namely genetic factors amounting to 14 respondents (35%), nutritional intake factors affecting 40 respondents (100%), immunization factors totaling 31 respondents (77.5%), infection factors totaling 14 respondents (35%). Parenting also emerged as a crucial element, with 20 respondents (50%). The results of this study provide holistic insight into the factors that play a role in the motor development of children aged 1-3 years. The implications of these findings could be used to support more effective interventions in promoting health and development in children